Extraordinary negative thermal expansion of monolayer biphenylene. (February 2022) - Li, Qingfang; Zhou, Jian; Liu, Gang; Wan, X.G.
Abstract: Recently, the two-dimensional biphenylene with sp 2 -hybridized carbon atoms has been successfully fabricated by experiment [ Science, 372, 852 (2021)]. In this paper, the thermal expansion properties of monolayer biphenylene (MBP) are investigated by using the density functional theory combined with Grüneisen's theory. It is found that MBP exhibits anisotropic and negative in-plane thermal expansion and the negative thermal expansion is up to 1000 K. Although MBP and graphene have similar sp 2 hybridized planar structure, the MBP exhibits significantly larger thermal contraction than graphene over a wide temperature range (0–1000K). At 300 K, the linear thermal expansion coefficient of MBP along the a -direction (1.10 × 10 −5  K −1 ) is about three times that of graphene (3.7 × 10 −6  K −1 ). The extraordinary negative thermal expansion not only originates from the ripple effect as in graphene only, but also the rigid unit modes are responsible for the thermal expansion behavior. Graphical abstract: Image 1